Financial constraints for R&D and innovation: New evidence from a survey experiment - Dirk Czarnitzki; Marek Giebel (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We utilize a new survey experiment to evaluate the existence and degree of financial constraints for R&D in the economy. The experiment does not only allow to deduct the presence of financial constraints, but also to evaluate their economic significance. Using data on German companies, we find that financial constraints for R&D exist but that their relevance might have been overestimated in the literature. Most R&D projects that have not been implemented because of financial constraints turn out to have low expected marginal rates of return. While this findings stands in some contrast to other studies, we also find several results that are in line with the literature: young firms are most constrained and the constraints occur at the intensive margin, i.e. our results do not suggest that non-innovative companies are deterred from innovation. Instead, highly innovative companies are restricted by the capital market.
Keywords: G30; O30; O31; O32; L21; 330; Innovation; Financial Constraints; Survey Experiment